Analysis of the Needs of Enrichment Books for Writing Javanese Culture-Themed Descriptive Texts by Integrating Humanist Values - Sinta Dayyana; Fathur Rokhman Fathur Rokhman; Wagiran Wagiran (Universitas Negeri Semarang, 2024)
Enrichment books on writing descriptive texts that collaborate with Javanese culture and the content of humanist character values are still minimal, the skill of writing descriptive texts is considered difficult, the influence of outside culture that causes a lack of knowledge about local culture, the number of criminal and violent cases that do not reflect the values of humanist character. This study aims to describe the need for enrichment books to write Javanese culture-themed descriptive texts by integrating humanist values and to determine the characteristics of enrichment books for writing Javanese culture-themed descriptive texts by integrating humanist values. This study uses the type of research (R&D), techniques used interview techniques, observation techniques, needs questionnaire techniques. The subjects in this study are students of class VII and class X, as well as educators of class VII and class X. Based on the results of the needs analysis, it is stated that the enrichment book for writing Javanese culture-themed description texts by integrating humanist values is needed in 4 aspects, namely material/content, presentation, language and readability, garfika. The characteristics of the enrichment book of material components include the principle of completeness, the principle of suitability, the principle of convenience, and the principle of adequacy. The presentation component includes the principles of collapse, systematic, straightforward, and easy to understand, the principle of developing social and spiritual attitudes. The components of language and readability include ethical, aesthetic, and functional principles, communicative principles, and spelling principles. The graphic components include the principles of the book cover, the principle of layout, the principle of lettering and numbering.